Strategic and Organizational Change - Cabrera-Suarez, Katiuska; Rivo-López, Elena; Lago-Peñas, Santiago (European Journal of Family Business, 2020)
Nowadays, family businesses, the predominant form of business worldwide, face an increasingly changing environment boosted by megatrends such as globalization, digitalization, artificial intelligence, climate change and sustainability. Along with this, are factors that play at a firm level such as stricter rules concerning transparency and compliance or the increasing importance of Corporate Social Responsibility (CSR). Therefore, new strategies and organizational changes are necessary to allow for greater adaptation to the new context. This special issue provides insights on these questions from a variety of perspectives. The work of Herna?ndez-Linares and Lo?pez-Ferna?ndez expands the current thinking on this process of adaptation by exploring the combined effects of three strategic orientations (entrepreneurial, learning, and market orientations) on the family firm ?s performance. The authors provide interesting contributions in terms of highlighting the importance of strategic orientations for value creation in enterprise organizations. They also provide empirical evidence that the family char- acter of the firm determines the relationship between strategic orientations and business performance, and offer some results on the effect of market orientation on firm performance in family firms versus non-family firms. Those differences in strategies are further ana- lysed within the setting of the business dimension in which financial and economic decisions are made. The contribution by Terro?n-Iba?n?ez, Go?mez-Miranda and Rodri?guez-Ariza, discusses the influence of that di- mension in their performance, comparing family and non-family firms. This interesting analysis of financial performance provides useful results. The study showsthat, unlike non-family firms, there is an inverted U- shaped relationship between the size of family SMEs and the value of certain economic–financial indicators, such as the return on assets, operating margin and employee productivity. This means that although the increase in the dimension of the family organizations is positively related to its performance, there are lim- its from which the value of certain economic–financial indicators can be negatively affected. The next paper contributes to the discussion of the family business’s role in the private health sector. Reyes-Santi?as, Rivo-Lo?pez and Villanueva-Villar, set out to identify the historical evolution of the family business in this sector, attempting to determine the variation and its contribution to the private health sector during the 1995-2010 period. The findings of this discussion provide family firms with an almost 60% survival level in this sector. Along with this, the au- thors provide some guidelines for future research con- cerning this higher degree of survival, why family firms are leading the concentration process taking place in the sector, as well as their strategies for super-spe- cialization in the services offered especially by family businesses in healthcare. The effect of family ownership and the character- istics of the board of directors on the implementation level of Enterprise Risk Management is an important topic. The article by Otero-Gonza?lez, Rodri?guez-Gil, Dura?n-Santomil and Tamayo-Herrera certainly adds to the discussion. In particular, their research shows that family businesses are less interested in implementing ERM, except when shareholders have greater control of the company and when professional investors are present in the company. Besides, the importance of a board of directors’ characteristics of in terms of risk taking is confirmed by observing that larger boards en- courage risk managers to be hired. The paper by Lorenzo-Go?mez looks at the barriers to change that are specific to the characteristics of family business, considering both the barriers that af- fect the perception of the need to undertake changes and the availability of resources to face those chang- es, and the barriers to implementing these changes within already consolidated organizations, where new routines are created to replace the existing ones. Thefindings suggest that the factors affecting these barri- ers include the generation at the head of the family business; the influence of interest groups, particularly in terms of the duality between the company and the family; and the participation level of professionals from outside the family. The final contribution by Aragon-Amonarriz and Iturrioz-Landart offers an interesting discussion on how family-responsible ownership practices enhance social responsibility in small and medium family firms. Their results reveal the positive relationships between the elements of family-responsible ownership in terms of succession management, financial resource allocation, professionalism and social responsibility, and ultimate- ly with the socially responsible behaviour of family SMEs. The challenges surrounding family business owners and the nuances around strategic and organizational decision making are together an area ripe for future research. The editors look forward to seeing future de- velopments on these topics that pay special attention to the influence of family characteristics and dynamics on the strategic and organizational change of family firms, and that draw on both quantitative and quali- tative research methodologies for the wider develop- ment of the field. Acknowledgements The papers published in this issue were presented at the “II Workshop of Family Business: Strategic and Organizational Change” at Ourense, Galicia, Spain, June, 13-14, 2019. The conference was organized by GEN group research (http://infogen.webs.uvigo.es/) and the Chair of Family Business of the University of Vigo, and was sponsored by the AGEF (Galician Family Business Association), Inditex Group, IEF (Spanish Family Firm Institute), and with ECOBAS group as collaborator. Thanks for their invaluable support. We are also very thankful of all other participants at the conference.